Efficacy of vigorous physical activity as an intervention for mitigating depressive symptoms in adolescents and young adults: a comprehensive systematic review and meta-analysis - Yang, Wei; Chen, Huijing; Liu, Wei; Qu, Sheng; Ge, Yao; Song, Jin (Frontiers in Behavioral Neuroscience, 2025)
PurposeThis study aimed to evaluate the effectiveness of vigorous physical activity as an intervention for alleviating depressive symptoms among adolescents and young adults.MethodsA comprehensive search on systematically reliable databases was carried out, and studies running till August 2023 were considered in this study. The articles included in this meta-analysis assessed the impact of exercise interventions on depressive symptomatology in adolescents and young adults. Two independent investigators screened the studies, extracted data, and evaluated quality.ResultsPhysical activity produced an important reduction in depressive symptoms [SMD] = −4.23, 95% CI: −7.02, −1.44, p = 0.0001; a moderate effect size in both the adolescent population with clinical depression and adolescents who presented with subclinical depressive symptoms. Notably, vigorous physical exercise worked most favorably for adolescent depressive symptomatology, while moderate-intensity exercise was the best choice for adolescents with diagnosed clinical depression.ConclusionThis meta-analysis suggests that vigorous physical activity could reduce depressive symptoms in adolescents and young adults. However, further studies are needed to provide clearer recommendations regarding the type, duration, and intensity of exercise necessary to treat clinical depression in this population.